STRATEGI SMART LEARNING BERBASIS BIG DATA PADA PENGAJARAN DATABASE - Fahrina Aulia Purba; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Information technology has changed the world of education, including the way of learning and teaching. This research aims to develop big data-based smart learning strategies that can be applied in teaching database in higher education institutions. Two major problems in teaching practical courses such as database are low student engagement and non-optimal utilization of learning data to support effective teaching strategies. This research utilized a qualitative descriptive approach, which was used to investigate the related literature. According to the research results, five main approaches were identified: student learning pattern analysis, adaptive material adjustment, project-based learning with real data, personalized learning advice, and learning progress visualization. This research offers conceptual and practical contributions in the development of big data-based teaching models in practice-based courses by integrating data from LMS, learning social media, and academic evaluation to create contextual, adaptive, and student-centered learning.